The usage of the paris classification system in urine cytology in the diagnosis of non-muscle-invasive bladder cancer: a retrospective single-center study - Perttu Saarinen; Otto Jokelainen; Liida Ruotsalainen; Essi Ikonen; Timo K. Nykopp (Discover Oncology)
Abstract Purpose This retrospective single-center study aimed to determine the correlation between The Paris System (TPS) urine cytology classification, cystoscopy findings, and non-muscle-invasive bladder cancer diagnosis. In addition, we sought to identify factors that might explain the abnormal cytology classification in cases in which no malignancy was detected. Methods A Total of 855 patients evaluated with urine cytology between 2017 and 2020 at Kuopio University Hospital were included. Histological diagnoses and urinalysis results were correlated with cytology (TPS). Chi-squared and Fisher’s exact tests were used to calculate statistical significance. Results In the absence of exophytic tumors on cystoscopy, the risks of bladder cancer was 0.1% for NHGUC, 1.5% for AUC, 22.7% for SHGUC, and 83.3% for HGUC. Positive urinalysis corresponded to lower cytological diagnostic categories in both males and females. A statistically significant difference was observed in males with respect to moderate pyuria, hematuria, and higher cytological categories. Conclusions This study provides evidence that a biopsy or follow-up may not be necessary for patients without a prior history of urothelial carcinoma and without exophytic tumors observed on cystoscopy, when the cytological diagnosis is NHGUC or AUC. Furthermore, concurrent hematuria and pyuria may result in a higher cytological classification.